2017
DOI: 10.1038/cr.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

PKR activation and eIF2α phosphorylation mediate human globin mRNA splicing at spliceosome assembly

Abstract: Short elements in mammalian mRNA can control gene expression by activating the RNA-dependent protein kinase PKR that attenuates translation by phosphorylating cytoplasmic eukaryotic initiation factor 2α (eIF2α). We demonstrate a novel, positive role for PKR activation and eIF2α phosphorylation in human globin mRNA splicing. PKR localizes in splicing complexes and associates with splicing factor SC35. Splicing and early-stage spliceosome assembly on β-globin pre-mRNA depend strictly on activation of PKR by a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(81 citation statements)
references
References 44 publications
3
78
0
Order By: Relevance
“…Early in vitro studies identified cellular RNAs with secondary structure as PKR regulators. These include 3 0 -untranslated region (UTR) of α-tropomyosin (Davis & Watson, 1996), stem-loop structure in the 3 0 -UTR of TNF-α mRNA (Osman, Jarrous, Ben-Asouli, & Kaempfer, 1999), 5 0 -pseudoknot structure of IFN-γ mRNA (Ben-Asouli, Banai, Pel-Or, Shir, & Kaempfer, 2002), and RNA activator elements of β-globin pre-mRNAs (Ilan et al, 2017) (Table 2). Although interesting, it should be recalled that their action on PKR is mostly based on in vitro data and their genuine cellular roles need to be validated.…”
Section: Cellular Rnas That Controls Pkrmentioning
confidence: 99%
See 1 more Smart Citation
“…Early in vitro studies identified cellular RNAs with secondary structure as PKR regulators. These include 3 0 -untranslated region (UTR) of α-tropomyosin (Davis & Watson, 1996), stem-loop structure in the 3 0 -UTR of TNF-α mRNA (Osman, Jarrous, Ben-Asouli, & Kaempfer, 1999), 5 0 -pseudoknot structure of IFN-γ mRNA (Ben-Asouli, Banai, Pel-Or, Shir, & Kaempfer, 2002), and RNA activator elements of β-globin pre-mRNAs (Ilan et al, 2017) (Table 2). Although interesting, it should be recalled that their action on PKR is mostly based on in vitro data and their genuine cellular roles need to be validated.…”
Section: Cellular Rnas That Controls Pkrmentioning
confidence: 99%
“…Ben-Asouli et al, 2002;Cohen-Chalamish et al, 2009) β-Globin pre-mRNAs Activation Unknown(Ilan et al, 2017) …”
mentioning
confidence: 99%
“…The question remains how infection signals the switch to an alternative "ribosome-engaged" transcriptome? PKR-mediated splicing has been previously reported 74 ; however, we were unable to link PKR activation to our change in variant expression. Further studies will be required to home-in on the signalling axis that mediates increased expression of the short Inpp5e transcript.…”
Section: Figure 5 Inpp5e Functions By Impairing Hsv1 Virion Attachmementioning
confidence: 56%
“…4F). PKR activation has been previously shown to modulate mRNA splicing 47 ; therefore we asked if induction of the short Inpp5e variant was dependent on this kinase. Although we could re-capitulate the poly(I:C)-mediated induction of the short variant in wildtype mouse embryonic fibroblasts (MEFs), there was a similar induction in their PKR-null counterparts 48,49 , suggesting that the short variant induction is PKRindependent ( Fig.…”
Section: Commonly Upregulated Genes Are De-repressed At the Level Omentioning
confidence: 99%
“…RNA-dependent protein kinase R (PKR) is an intracellular sensor of stress that has recently been shown to also be essential for globin gene expression generally (Ilan et al, 2017). It could potentially also act in conditions of cellular stress to modulate haemoglobin expression, while in Drosophila knockdown of a globin gene expressed in the trachea reduces survival under hypoxia (Gleixner et al, 2016;Harrison et al, 2018), presumably due to a role in providing adequate oxygen levels.…”
Section: A Haemoglobin Response To Cr In D Magnamentioning
confidence: 99%